Long-range air-host plasmonic propagation with subwavelength confinement - Yue, Kun; Feng, Xialian; Yu, Jiaxin; Gu, Fuxing (Frontiers in Physics, 2024)
Confining light at a subwavelength scale is important for building ultracompact opto-electronic networks. Plasmonic waveguides are good candidate devices for this purpose. However, the oscillation of electrons relating to surface plasmon polaritons causes energy dissipation, which limits the propagation length and thus reduces the waveguide performance. Here, we design a low-loss plasmonic waveguide composed of a nanowire dimer structure on a metal substrate, in which the dominant modes are localized within the air gap between the nanowires and referred to as air-host plasmonic modes. The use of air instead of dielectric materials as the host medium can reduce ohmic loss and avoid the dispersion effect of dielectric. When the constructed nanowires have a diameter less than 100 nm, the air-host mode has subwavelength-scale confinement and a propagation length of ~100 μm, which has broad application prospects for the construction of ultracompact plasmonic devices.